“Inducción de la embriogénesis somática en hojas inmaduras de sacha inchi (plukenetia volubilis L.)” - Guerrero Abad, Juan Carlos (2007)
With the objective of developing a suitable methodology for the sacha inchi (Plukenetia vo/ubilis L.) somatic embryogenic induction, explants of immature leaf of 25-26 mm were used, two study were evaluated, the first one consisted of the evaluation of the synchronization of the induction time, using 05 treatments with different concentrations of thidiazurón (0.000, 0.003, 0.005, 0.008, 0.010 mg/I), with base culture media of the mineral compounds M&S (1962) supplemented with Vit DKW, 2.0 mg/I 2,4-0, 2.0 g/I phytagel; the same media for the second study 12 treatments witch different cornbinations of two factors [citoquinina (thidiazurón) - times of induction] were evaluated. For the development of the somatic embryogenesis process and especially for the second study (MICE) three means of culture where used, media of induction of embryogenic callus, media of secondary growth of callus (MCSC) anda media of development of embroides (MDE). For the induction process of embryogenic callus of the first and second study, the explants were incubated in darkness, for the second study the secondary growth of callus the period of darkness was limited to 6 and 10 days respectively, to be cultivated aftermath in the culture media MEO for a time of 14 days in darkness and then submitted to light. The percentage of induction of callus evaluated in all the treatments of the first study demonstrates that up to 9 days of induction 100 % of callogenic reactivity exists, the growth of callus evaluated in all the treatments of the second study demonstrates that a proflt of average callus in 4.46 to 4.97 mg/day exists, the appearance of pro-embryonic globular stages of sacha inchi was confirmad in the T2, T4, T9 and T10, and the conformation of the first embryonic stage (globular stage) was confirmed in the T4. lt is necessary to mention that during the development of the process of somatic not embriogenic callus of creamy and crystalline thin irregular consistency were identified. The rhizogenesis as a product of the indirect organogenesis in the immature leaves was one of the most important observations of this investigation.